The trauma and the triumph : gender and partition in eastern India - Bagchi, Jasodhara; Dasgupta, Subhoranjan (Kolkata : Stree ; Mumbai : Distributed by Popular Prakashan, 2003)
Contributed articles on the sufferings of women during the partition of Bengal in 1947; includes personal narratives.
Includes bibliographical references (p. [261]-268) and index.
Keywords: Bengal (India) -- History -- Partition, 1947.; Women -- India -- Bengal -- History